Objection my Lord: legal practice demystified - Lubogo, Isaac Christopher (Jescho Publishing House, 2022)
Having received a brief of the client’s case, and identified legal issues. You should develop a Checklist to enable you pick necessary legal information you would need to advise the client and also in case of court action, sufficient information to support the action and also the mode of Commencement. In developing one you can be guided by the Substantive legislation on the matter, case law and even the CPR for example Check list No Standard template Make sure it covers the details of the workshop question There and general things in the personal details 0.7. 1 is also a guiding factor.
Keywords: Legal practice - Uganda